Introduction - Nadine Tkatchevskaia, Jenny David & (Glendon Journal of International Studies, 2014)
Introduction par co-éditrices Jenny David & Nadine Tkatchevskaia<!--[if gte mso 9]> 72 544x376 <![endif]--> Introduction by co-managing editors Jenny David & Nadine Tkatchevskaia